Rancang Bangun Pagar Otomatis Berbasis Iot dengan Kendali Web dan Remote Inframerah Menggunakan Esp8266 - Sujono; Muchammad Iqbal Aprilianto (Pusat Riset dan Inovasi Nasional, 2025)
The advancement of Internet of Things (IoT) technology has driven automation in various aspects of life, including home security systems. In this final project, an IoT-based automatic gate control system was designed and developed, which can be controlled via a website and an infrared remote. The system uses an ESP8266 microcontroller connected to the internet to send and receive data to and from a database. When the Wemos is connected online, users can control the gate in real-time through a web interface that displays the current gate status and device connectivity. If the Wemos is offline, the system can still be operated using the infrared remote, and the last command will be synchronized back to the database once the connection is restored. Additionally, the system is powered by a 12V battery that can be recharged using a solar panel, making it energy-efficient and capable of operating independently. Testing was carried out using the black box method, covering website functionality, remote control, infrared signal range, and power efficiency of the battery and solar panel. The test results show that the system performs well both online and offline, providing an efficient, safe, and eco-friendly automation solution for gates.